EFFECT OF COMMERCIAL SULFURIC ACID, PHOSPHORUS, IRON AND ZINC APPLICATION ON PHOSPHORUS, IRON, ZINC AVAILABILITY IN CALCAREOUS SOIL AND YIELD OF CABBAGE - Ahmed, Firas W.; AL-Tameemi, Ali J. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A field experiment was conducted to evaluate the effect of commercial Sulfuric acid, phosphorous, iron, and zinc application on Phosphorus, Iron, Zinc Availability in Calcareous Soil and Yield of Cabbage (Brassica oleracea L.), in an agricultural field at College of Agricultural Engineering Sciences / University of Baghdad / Iraq during the autumn season of 2021, in silty loam soil using Split Plot Design in a randomized complete block design (RCBD) with three replicates. Sulfuric acid H2SO4 added with irrigation water at 0 and 2 ml L-1. Phosphorus was added to the soil at (0, 50, 75 and 100%) from the recommended level (65 kg P ha-1) as TSP (20% P), iron was added to the soil at 10 kg Fe ha-1 as FeSO4.7H2O (20% Fe), and zinc was added to the soil at 5 kg Zn ha-1 as ZnSO4.7H2O (23 %Zn). Results showed a significant effect of adding commercial sulfuric acid H2SO4, Phosphorus and zinc fertilizers to the soil (2 ml L-1 + 65 kg P ha-1 + 5 kg Zn ha-1) after 30 days of planting and after harvest and achieved available phosphorus of 27.87 and 22.48 mg P kg-1 soil and available iron of 7.197 and 7.210 mg Fe kg-1 soil and available zinc of 1.907 and 1.883 mg Zn kg-1 soil respectively, and plant yield of 70.64 Mg ha-1 with an increase of 81.12 % compared to control.